Polynomial interpolation for inversion-based control. (November 2020) - Minari, Andrea; Piazzi, Aurelio; Costalunga, Alessandro
Highlights: Inversion-based control to solve a generalized feedforward regulation problem. An interpolating polynomial to smoothly join two distinct steady-state outputs. Minimization of the transition time to reduce the delay of the future desired output. Offline polynomial basis to speed up online implementation. Event-based control made possible by iterative implementation. Abstract: To help to achieve high performances in the regulation of linear scalar (SISO) nonminimum-phase systems, an inversion-based (feedforward) control method is proposed. The aim is designing an inverse input to smoothly switch from a current, arbitrary, steady-state regime to a new, future, desired steady-state output. A new-found polynomial basis solves the related interpolation problem to join the current output to the future one while ensuring the necessary or desired smoothness. The (interpolation) transition time can be minimized in order to optimally reduce the delay with which the desired output occurs. By applying a behavioral stable inversion formula to the overall smoothed output, detailed expressions of the inverse input are finally derived. A simulation of a flexible arm rotating in the horizontal plane exemplifies the presented method.